Bioengineering Human Myocardium on Native Extracellular Matrix. Issue 1 (8th January 2016) - Guyette, Jacques P.; Charest, Jonathan M.; Mills, Robert W.; Jank, Bernhard J.; Moser, Philipp T.; Gilpin, Sarah E.; Gershlak, Joshua R.; Okamoto, Tatsuya; Gonzalez, Gabriel; Milan, David J.; Gaudette, Glenn R.; Ott, Harald C.
Abstract : Rationale: : More than 25 million individuals have heart failure worldwide, with ≈4000 patients currently awaiting heart transplantation in the United States. Donor organ shortage and allograft rejection remain major limitations with only ≈2500 hearts transplanted each year. As a theoretical alternative to allotransplantation, patient-derived bioartificial myocardium could provide functional support and ultimately impact the treatment of heart failure. Objective: : The objective of this study is to translate previous work to human scale and clinically relevant cells for the bioengineering of functional myocardial tissue based on the combination of human cardiac matrix and human induced pluripotent stem cell–derived cardiomyocytes. Methods and Results: : To provide a clinically relevant tissue scaffold, we translated perfusion-decellularization to human scale and obtained biocompatible human acellular cardiac scaffolds with preserved extracellular matrix composition, architecture, and perfusable coronary vasculature. We then repopulated this native human cardiac matrix with cardiomyocytes derived from nontransgenic human induced pluripotent stem cells and generated tissues of increasing 3-dimensional complexity. We maintained such cardiac tissue constructs in culture for 120 days to demonstrate definitive sarcomeric structure, cell and matrix deformation, contractile force, and electrical conduction. To show that functional myocardial tissue of human scale can be built on this platform, we then partially recellularized human whole-heart scaffolds with human induced pluripotent stem cell–derived cardiomyocytes. Under biomimetic culture, the seeded constructs developed force-generating human myocardial tissue and showed electrical conductivity, left ventricular pressure development, and metabolic function. Conclusions: : Native cardiac extracellular matrix scaffolds maintain matrix components and structure to support the seeding and engraftment of human induced pluripotent stem cell–derived cardiomyocytes and enable the bioengineering of functional human myocardial-like tissue of multiple complexities. Abstract : Supplemental Digital Content is available in the text.